Destruction of Mycotoxins in Poultry Waste under Anaerobic Conditions within Methanogenesis Catalyzed by Artificial Microbial Consortia - Elena Efremenko; Olga Senko; Olga Maslova; Ilya Lyagin; Aysel Aslanli; Nikolay Stepanov (Toxins, 2023)
To reduce the toxicity of modern feeds polluted by mycotoxins, various sorbents are added to them when feeding animals. A part of the mycotoxins is excreted from the body of animals with these sorbents and remains in the manure. As a result, bulk animal wastes containing mixtures of mycotoxins are formed. It is known that it is partially possible to decrease the initial concentration of mycotoxins in the process of anaerobic digestion (AD) of contaminated methanogenic substrates. The aim of this review was to analyze the recent results in destruction of mycotoxins under the action of enzymes present in cells of anaerobic consortia catalyzing methanogenesis of wastes. The possible improvement of the functioning of the anaerobic artificial consortia during detoxification of mycotoxins in the bird droppings is discussed. Particular attention was paid to the possibility of effective functioning of microbial enzymes that catalyze the detoxification of mycotoxins, both at the stage of preparation of poultry manure for methanogenesis and directly in the anaerobic process itself. The sorbents with mycotoxins which appeared in the poultry wastes composed one of the topics of interest in this review. The preliminary alkaline treatment of poultry excreta before processing in AD was considered from the standpoint of effectively reducing the concentrations of mycotoxins in the waste.